The Role Of Caspase-Activated Dnase (Cad) In Chromosome Breaks During Oxidative Stressinduced Apoptosis - Boon, Siaw Shi (University Malaysia Sarawak, UNIMAS, 2009)
Chromosomal rearrangement, such as additions, deletions, translocations and inversions are phenomena commonly observed in various types of cancers including leukaemia and nasopharyngeal carcinoma (NPC). In leukaemia, structural rearrangements of the Mixed Lineage Leukaemia (MLL) gene at 11q23 have been reported extensively. In NPC, chromosomal deletions and additions are observed where one of the common deletion sites is at 11q23. However, the precise site of deletion has not been mapped to the gene level. Furthermore, mechanism leading to chromosome rearrangements in NPC is unknown. In the case of leukaemia, there are various mechanisms being proposed where apoptotic nuclease is one of them. Harmful or mutated cells undergo autonomous elimination through programmed cell death or apoptosis. However, dysregulation of apoptosis can result in many diseases such as cancer. Morphologically, apoptotic cells are characterised by cells dislodgement, membrane blebbing, condensation of cytoplasm and nucleus, as well as cellular fragmentation into membrane apoptotic bodies. In addition, apoptotic cells DNA integrity is changed where chromatin loop domains are released and may be followed by internucleosomal cleavage. This leads to DNA ladder formation typically seen on agarose gel. During apoptosis, there are a few DNases responsible for DNA fragmentation, in which one of them is the Caspaseactivated DNase (CAD). In normal growing cells, CAD co-exists with its inhibitor, ICAD, and remains inactive. ICAD also functions as a chaperone for CAD and is essential for the correct folding of CAD protein. When triggered by apoptotic stimuli, ICAD is cleaved by caspase-3, releasing the active CAD. Activated CAD will then cleave the genomic DNA. Mutation of CAD and ICAD may result in reduction of internucleosomal cleavage. This is because mutated CAD does not form stable complex with the DNA. Moreover, mutated ICAD, which is resistant to caspase-3 cleavage, is bound to CAD permanently, thus, in spite of the presence of apoptotic stimuli, CAD does not become activated. In vitro studies showed that a variety of cells, including tumour cell lines and normal cell types undergo apoptosis when they are exposed to oxidative stress. Oxidative stress occurs when cells are injured due to elevated production of reactive oxygen species (ROS), such as hydrogen peroxide, H2O2. Excessive ROS production leads to direct DNA damage, which can result in induction of apoptosis in severely damaged cells. We hypothesized that, during stress-induced apoptosis, CAD may cause the initial chromosome break which eventually leads to result in chromosomal rearrangement of the MLL breakpoint cluster region (bcr). Our dose response experiments showed that, NPC (SUNE1) and cervical cancer (HeLa) cell line treated with 50 μM and 100 μM H2O2 respectively for 20 hours showed apoptotic features. Cleavage within the MLL bcr was further confirmed via Inverse Polymerase Chain Reaction (IPCR). In order to study the role of CAD and ICAD, these genes were expressed transiently and stably in mammalian cell lines. Human and murine CAD genes as well as murine ICAD genes were subcloned into 2 expression vectors, namely pcDNA and pTracer. The role of CAD was studied by using four approaches. Firstly, CAD was overexpressed in mammalian cell line but the result was inconclusive. This may be due to the CAD expressed was not functional. Secondly, mutant ICAD was overexpressed to inhibit CAD directly. Mutant ICAD which was resistant to caspase-3 cleavage bound to endogenous CAD and hence CAD could not execute its DNase activity. However, the IPCR result showed that mutant ICAD did not reduce cleavage within the MLL bcr. Therefore, third approach was designed where CAD was inhibited indirectly by using caspase inhibitor. Caspase inhibitor should block the activation of caspase-3 and thus block CAD activation. However, our result showed no significant difference between cells with and without caspase inhibition. This could be due to inefficient uptake of caspase inhibitor into the cells. There might be other DNase responsible to DNA cleavage within the MLL bcr, such as Endonuclease G (Endo G), Apoptosis-induced Factor (AIF) and so on. Chromosomal breakage within the MLL bcr might not solely dependent on the caspase pathway upon oxidative stress-induced apoptosis. In the last approach, CAD and/or ICAD was overexpressed. As confirmed by Western blotting, coexpression of CAD and ICAD resulted in CAD expression. Overexpression of ICAD alone was sufficient to induce high levels of endogenous CAD expression. From the IPCR result, it showed that CAD expression enhances cleavage within the MLL bcr upon oxidative stress. In conclusion, oxidative stress can induce apoptosis in mammalian cell lines. CAD may be involved directly in the cleavage of the MLL bcr. Chromosome rearrangements via the apoptotic process may be dependent on the chromatin structure. In order to further strengthen the hypothesis, involvement of CAD in the cleavage of other genes should also be studied.